PENGARUH MODEL PEMBELAJARAN POE (PREDICT-OBSERVE-EXPLAIN) BERBASIS SAINS TERNOLOGI MASYARAKAT TERHADAP HASIL BELAJAR SISWA TENTANG DAUR AIR DI KELAS IV UPT SPF SD INPRES MACCINI SOMBALA 1 - Nadya Permata Putri Bhoes (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low student learning outcomes on the topic of the water cycle, primarily due to the use of conventional teaching methods that are less engaging and lack contextual relevance. To address this issue, the Predict-Observe-Explain (POE) learning model based on Science-Technology-Society (STS) was implemented to enhance students’ understanding through active involvement and the integration of scientific concepts with real-life applications. The purpose of this study was to examine the effect of the POE learning model based on STS on the learning outcomes of fourth-grade students in the water cycle topic at UPT SPF SD Inpres Maccini Sombala 1. The study employed a quasi-experimental design with a control group pretest-posttest format. The population consisted of 56 fourth-grade students divided into two groups: 28 students in the experimental group and 28 in the control group. Data collection techniques included observation, documentation, and multiple-choice tests administered before and after the intervention. The data were analyzed using descriptive and inferential statistics. The findings revealed that the experimental group’s average posttest score increased significantly from 64.00 to 84.43, while the control group’s score improved from 54.57 to 75.71. An independent sample t-test yielded a significance value of 0.000 < 0.05, indicating a statistically significant difference in learning outcomes between the two groups. Thus, it can be concluded that the POE learning model based on STS is effective in improving students’ understanding of the water cycle. Moreover, it promotes scientific literacy and awareness of water's importance and its technological management in line with 21st-century education values.